Treatment of Early-onset Scoliosis: Similar Outcomes Despite Different Etiologic Subtypes in Traditional Growing Rod Graduates. Issue 1 (4th January 2022) - Akbarnia, Behrooz A.; Pawelek, Jeff B.; Hosseini, Pooria; Salari, Pooria; Kabirian, Nima; Marks, David; Shah, Suken A.; Skaggs, David L.; Emans, John B.; Elsebaie, Hazem; Thompson, George H.; Sponseller, Paul D.
Abstract : Background: It is unclear whether traditional growing rod (TGR) treatment outcomes vary by early-onset scoliosis (EOS) subtype. The goal of this study was to compare radiographic outcomes and complications of TGR treatment by EOS subtype. Methods: We queried an international database of EOS patients from 20 centers to identify "graduates" who had (1) undergone primary TGR treatment from 1993 to 2014; (2) completed TGR treatment; and (3) had an uneventful clinical examination within 6 months after completion of TGR treatment with no anticipated further intervention. We included 202 patients in 4 etiologic subgroups: neuromuscular (n=65), syndromic (n=57), idiopathic (n=52), and congenital (n=28). Mean age at surgery was 7.1 years (range, 1.6 to 14.9 y); mean duration of follow-up was 8 years (range, 2 to 18.6 y). The groups did not differ by mean age, body mass index, sex, number of lengthenings, or duration of follow-up. The following preoperative differences were significant: (1) greater mean major curve in the neuromuscular versus idiopathic subgroup; (2) shorter spinal height (T1-S1) in the congenital versus idiopathic subgroup; and (3) smaller proportion of ambulatory patients in the neuromuscular subgroup versus all other subgroups. Results: We found no significant differences among subgroups in mean major curve correction or changes in thoracic height (T1-T12), spinal height, or global kyphosis at any point. Rates of deep surgical site infection, implant-related complications, and neurological complications were not different among subgroups. The medical complication rate was significantly lower in the idiopathic group compared with the other groups. Conclusions: Major curve correction and spinal and thoracic height increases did not differ significantly at any point by EOS subtype. Rates of deep surgical site infection, implant-related complications, and neurological complications did not differ by subtype. Except for the lower rate of medical complications in the idiopathic group, our findings suggest that, after TGR treatment, patients can expect similar outcomes regardless of their EOS subtype. Level of Evidence: Level III, therapeutic.